The vulnerability of thermoelectric power generation to water scarcity in China: Current status and future scenarios for power planning and climate change. (1st June 2016) - Zheng, Xinzhu; Wang, Can; Cai, Wenjia; Kummu, Matti; Varis, Olli
Graphical abstract: Highlights: We assess the severity and location of water and electricity conflicts in China. An index was constructed to measure the vulnerability of thermoelectric plants. Power generation in seven regions is highlighted as vulnerable to water shortage. Decreasing water withdrawal intensity alone cannot solve the vulnerability concerns. Regions where climate change will aggravate the vulnerability are highlighted. Abstract: Although China has experienced a wide variety of regional conflicts between water scarcity and electricity generation, there are few comprehensive quantifications that explicitly reveal the location and severity of these conflicts. Triggered by the soaring need for such information, we performed a high-resolution evaluation and projection of the spatial vulnerability of thermoelectric power generation to water scarcity problems. The study provides a comprehensive assessment by incorporating thermoelectric plants' reliance on water, local water supply stress and future impacts brought about by planning and climate change into the analysis simultaneously. To measure the vulnerability of thermoelectric plants to water scarcity, a vulnerability index was constructed and multi-disciplinary approaches were integrated to quantify this index. Seven hotpots in North China were highlighted as power-vulnerable to water scarcity currently. In order to fulfill the power generation target in the future, less-vulnerable watersheds identified by this study are suggested to become the sites of future power plants. Besides, lowering the water withdrawal intensity of power plants alone is not enough to solve the vulnerability concerns. Instead, it is necessary to implement other water management, including water rights allocation in the trans-boundary river basins. This paper also highlights regions where climate change will threaten power generation by decreasing the water availability. These insights are valuable for adding the alleviation of water and electricity conflicts to climate change adaptation agenda.